2016
DOI: 10.1002/14651858.cd012199
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to improve water, sanitation, and hygiene for preventing soil-transmitted helminth infection

Abstract: This is the protocol for a review and there is no abstract. The objectives are as follows:To assess the effectiveness of water, sanitation, and hygiene interventions to prevent soil-transmitted helminth infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 43 publications
2
23
0
Order By: Relevance
“…The well-documented benefits of household and community WASH interventions for a range of infectious disease outcomes15 16 18–20 22 24 59–65 and consistently protective effect of the combined interventions included in this systematic review and scoping review support the widely held, if poorly researched view that WASH in HCFs are a fundamental component of effective IPC. While this view may be widely held, the reality in LMICs is that WASH infrastructure and interventions are often overlooked.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The well-documented benefits of household and community WASH interventions for a range of infectious disease outcomes15 16 18–20 22 24 59–65 and consistently protective effect of the combined interventions included in this systematic review and scoping review support the widely held, if poorly researched view that WASH in HCFs are a fundamental component of effective IPC. While this view may be widely held, the reality in LMICs is that WASH infrastructure and interventions are often overlooked.…”
Section: Discussionsupporting
confidence: 52%
“…Safe water, sanitation and hygiene (WASH) are key public health interventions 13–25. An adequate quantity and quality of water, facilities for safely managing excreta and healthcare waste, and the application of hygienic practices such as hand hygiene and environmental cleaning, are essential to the functioning of any HCF 26 27.…”
Section: Introductionmentioning
confidence: 99%
“…The limited findings reported here are similar to findings of other studies. A recent review of brief interventions conducted in schools, for example, found that while they outperformed assessment only control conditions, they did not produce significant effects when compared to information-only interventions (Carney, Myers, Louw, & Okwundu, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…The mechanical transmissions of parasitic diseases by cockroaches are neglected. However, cockroaches can be potential reservoirs and possible vectors for intestinal parasites [11][12][13]. Moreover, epidemiological information on species composition of cockroaches, their potential as mechanical vectors of intestinal parasites and associated factors is very limited in Ethiopia.…”
Section: Species Composition Of Cockroaches Their Potential As Mechamentioning
confidence: 99%